Activities of the Ufa Local Branch of the Russian Red Cross Society during the First World War - R. I. Kantimirova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The main directions of activity of the Ufa local branch of the Russian Red Cross Society during the First World War are considered. It is described that during wartime an important event was the organization by the Ufa local branch of an extensive collection of donations in order to create infirmaries for the wounded. In addition, feasible material assistance was provided in the form of one-time benefits to the wounded and injured soldiers. The study of materials from the reviews of the Ufa province showed that the Ufa local branch organized and sent stage infirmaries to the army. It is noted that special courses to work in them, which successfully trained the staff of sisters of mercy, were created. It is reported that many of them were presented with awards for their selfless and valiant work. The study of all-Russian and regional statistical materials made it possible to conclude that at the initial stage of the war, the fund of the Ufa local branch of the Russian Red Cross Society received significant financial allocations on the basis of public charity, which were used to solve the necessary wartime tasks. It is emphasized that by 1917, amid the growing crisis, the amount of donations significantly decreased, which significantly complicated the further activities of the Society both on a national scale and at the regional level.